Efektivitas Penerapan E-Government Berbasis Aplikasi Ferizy Di Pelabuhan Pamatata Kabupaten Selayar - Muh Taufik; Haerana; Syukri (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
Abstract: The implementation of e-government through digital technology is a strategic initiative to enhance the quality of public services. One such initiative is the adoption of the Ferizy application as a ferry ticket booking system at Pamatata Port in Selayar Regency. This study analyzes the effectiveness of e-government implementation through the Ferizy application in the context of public service delivery at Pamatata Port. Employing a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation involving ASDP officers and ferry service users. The effectiveness analysis was conducted using five indicators proposed by Sutrisno: program understanding, target accuracy, timeliness, goal achievement, and real change. The findings indicate that the implementation of the Ferizy application has been effective in improving service accessibility, transparency, and efficiency in the ticket purchasing process. Nevertheless, several challenges persist, including limited digital literacy among certain segments of the population, technical difficulties within the application, and prolonged queues for ticket verification at the port. In conclusion, the study demonstrates that implementing e-government through the Ferizy application has had a positive impact on public service delivery. However, further efforts are required to strengthen socialization, provide user assistance, and improve system functionality and operational coordination. Keywords: Effectiveness, E-Government, Ferizy, Public Services, Pamatata Port